Multi‐shelled Hollow Metal–Organic Frameworks - Liu, Wenxian; Huang, Jijiang; Yang, Qiu; Wang, Shiji; Sun, Xiaoming; Zhang, Weina; Liu, Junfeng; Huo, Fengwei (Angewandte Chemie International Edition, 2017)
Hollow metal–organic frameworks (MOFs) are promising materials with sophisticated structures, such as multiple shells, that cannot only enhance the properties of MOFs but also endow them with new functions. Herein, we show a rational strategy to fabricate multi‐shelled hollow chromium (III) terephthalate MOFs (MIL‐101) with single‐crystalline shells through step‐by‐step crystal growth and subsequent etching processes. This strategy relies on the creation of inhomogeneous MOF crystals in which the outer layer is chemically more robust than the inner layer and can be selectively etched by acetic acid. The regulation of MOF nucleation and crystallization allows the tailoring of the cavity size and shell thickness of each layer. The resultant multi‐shelled hollow MIL‐101 crystals show significantly enhanced catalytic activity during styrene oxidation. The insight gained from this systematic study will aid in the rational design and synthesis of other multi‐shelled hollow structures and the further expansion of their applications. Promising MOF structures: Single‐crystalline multi‐shelled hollow metal–organic frameworks (MSHMs) were synthesized through step‐by‐step crystal growth and subsequent etching processes. The cavity size and shell thickness of each layer in the MSHMs was regulated through careful nucleation and crystallization of the metal–organic frameworks. The MSHM crystals show significantly increased catalytic activity.